Forage potential of selected Costa Rican corn varieties for grain - Sánchez Ledezma, William (2024)
Introduction. Corn (Zea mays) is widely used in animal feed, either as grain, green fodder or silage. Objective. To evaluate the yield and nutritional quality of 6 Costa Rican corn varieties selected for grain production. Materials and methods. The study was conducted at 4 experimental sites (Aguas Zarcas, Turrialba, San Luis de Monteverde and Guápiles) between September and December 2018. At each site, a randomized complete block design with 4 replications and 8 treatments (6 varieties and 2 corn hybrids). Plant height was evaluated, Dry Mass (DM) production, chemical composition and in vitro DM digestibility at forage harvest were evaluated. Results. Plant height and DM production were affected by treatments. Yields of the Costa Rican DM varieties EJN2, Upiav-G6, Los Diamantes 8843 and JSáenz (12.7-14 t.ha-1) were similar to the forage hybrid CLTHY002 (13.5 t.ha-1).Only DM and CP content varied in the treatments. Conclusions. The Costa Rican corn varieties EJN2, Los Diamantes 8843, JSáenz and Upiav-G6, have potential to be used as a forage source for animal feeding because they achieved yields and nutritive values like those obtained with the hybrids selected by Centro Internacional de Mejormiento de Maíz y Trigo (CIMMYT) for forage production.